The effectiveness of the pit and fissure sealant in the "Save our six" project Chiang Rai, Thailand. - อบสุวรรณ โคสิต (Thai Dental Public Health Journal, 2019)
The objective of this study was to compare prevalence of dental caries and the mean DMFT of the school children after 2 years of sealant program. The study group composed of 520 students of 8 years old who received 4 first molars sealant together with tooth brushing with fluoride toothpaste after lunch. The control group were 520 students who received only tooth brushing program. The result showed that DMFT of 4 first molars of study and control groups were 0.60 0.92 and 0.65 +0.99 respectively, which was significantly difference (p < 0.05). However, the prevalence of dental caries between these 2 groups was not significantly difference (p > 0.05).